2009
DOI: 10.1111/j.1440-1746.2009.05796.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment as first‐line therapy for pancreatic ascites and pleural effusion

Abstract: Endoscopic therapy offers an excellent therapeutic alternative in patients with pancreatic ascites and pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…These interventions are thought to decrease pancreatic secretions facilitating fistula closure and promote serosal apposition and healing 8. This approach has high failure rates of 40–60%,9 10 mortality rates of 17%1 2 and may be costly 11. Risk factors for failure of conservative therapy include severity of pancreatic duct disease seen on ERCP including the presence of more than one site of contrast extravasation and degree of biochemical abnormalities on admission labs including low serum sodium and serum albumin levels and a higher ratio of ascitic fluid protein to total serum protein levels 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions are thought to decrease pancreatic secretions facilitating fistula closure and promote serosal apposition and healing 8. This approach has high failure rates of 40–60%,9 10 mortality rates of 17%1 2 and may be costly 11. Risk factors for failure of conservative therapy include severity of pancreatic duct disease seen on ERCP including the presence of more than one site of contrast extravasation and degree of biochemical abnormalities on admission labs including low serum sodium and serum albumin levels and a higher ratio of ascitic fluid protein to total serum protein levels 10.…”
Section: Discussionmentioning
confidence: 99%
“…These stents facilitate healing of ductal disruptions either by partial obstruction of the main pancreatic duct or bypassing the pancreatic sphincter to reduce intraductal pressure and create preferential flow through the stent 1 6. ERCP has the potential complication of secondary infection of the ascites or pseudocysts and adequate precautions to minimise risk should be taken including limiting volume of contrast used and postprocedure antibiotic prophylaxis 11. A study by Bracher et al 6 describes seven of eight cases that underwent endoscopic placement of a transpapillary pancreatic duct stent with complete resolution of PA within 6 weeks of initial stent placement and no recurrence during a 14-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates of from 7% to 25% have been reported (14)(15)(16). Nevertheless, it has been suggested that pancreaticopleural fistulas may be best managed by ERCP-guided therapeutic intervention or by early surgical treatment (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is also the report that combined endoscopic and percutaneous rendezvous technique is the efficient method to reduce the pressure in cases of failure of endoscopic stenting 33) . Although stent therapy has been reported to be more invasive and carries a greater risk than medical therapy, it has been reported to be safer than surgical treatment 25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…The previous reports showed that ERCP is the most specific modality for identifying the pancreatic duct anatomy and the site of disruption. The reported advantage of ERCP is that it offers the opportunity for definitive therapy using an endoscopic stent, sphincterotomy, or nasopancreatic drainage 25,26) .…”
Section: Discussionmentioning
confidence: 99%